Maternal supplementation with chia oil attenuates hepatic metabolic disturbances in mice subjected to postnatal undernutrition - Leão, Estéfany Ribeiro; Konig, Isaac; Silva Marques, Sarah Melo; Candido, Geraldo de Sousa; Varaschin, Mary Suzan; Pimenta, Laura Cristina Jardim Pôrto; Castro, Isabela Coelho de (Frontiers in Nutrition, 2025)
BackgroundEarly postnatal undernutrition, leading to impaired growth and low body weight, has been associated with enduring metabolic alterations that may persist into adulthood. We proposed that plant-based ω-3 fatty acids, as in maternal supplementation, attenuate metabolic alterations induced by postnatal dietary restriction, such as glucose disturbances and oxidative stress.MethodsTo test this, we investigated the effects of maternal supplementation with two distinct doses of Chia Oil (ChO) (2.5 or 5 g/kg body mass) on metabolic parameters in BALB/c mice subjected to postnatal undernutrition. The undernutrition model was created by increasing the litter size to 15–16 pups, forming the undernutrition (UN) group. These UN groups received maternal ChO supplementation at 2.5 g/kg or 5 g/kg b.m., labeled as UN2.5 and UN5, respectively.ResultsBy day 21, the UN5 group showed less weight gain compared to the UN2.5 group. At 120 days, glucose tolerance tests revealed a lower area under the curve in both supplemented groups compared to the UN animals. A maternal dose of 5 g/kg b.m. of ChO was linked to more favorable oxidative stress markers, suggesting this effect is not due to changes in antioxidant enzymes like superoxide dismutase and catalase, which remained stable in the liver tissue in this model. This dose provided a slight benefit in reducing metabolic changes, with the UN5 group showing lower total hepatic lipid levels. Additionally, histopathological analysis of the tissue revealed no alterations in the experimental groups.ConclusionThese observations suggest a protective role of maternal ChO supplementation at a dose of 5 g/kg b.w. against metabolic impairments induced by postnatal undernutrition.